TANTANGAN GENERASI Z DALAM MELESTARIKAN KAROMBI SEBAGAI ALAT MUSIK TRADISIONAL TORAJA DI LEMBANG BUNTU KARUA - Juvin Samel Selbato; Yustika (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study analyzes the impact of technological advancements on Generation Z's interest in learning and preserving traditional Toraja musical instruments, particularly the Karombi. Generation Z, growing up in the digital era, exhibits a high dependency on technology and tends to favor modern musical instruments over traditional ones. The main characteristics of Generation Z include technological proficiency, multitasking, and tolerance towards cultural differences, but they also have a tendency to neglect traditional cultural heritage such as the Karombi. The Karombi, a traditional Torajan musical instrument made of bamboo and fine thread, is now nearly extinct due to the lack of interest from the younger generation. Despite various efforts to document and preserve traditional musical instruments, changing interests driven by technological progress pose a significant challenge. This study emphasizes the importance of innovative strategies in teaching and promoting traditional musical instruments to Generation Z to ensure their preservation for the future